Domestication and Feed Restriction Programming Organ Index, Dopamine, and Hippocampal Transcriptome Profile in Chickens - Chen, Siyu; Yan, Chao; Xiao, Jinlong; Liu, Wen; Li, Zhiwei; Liu, Hao; Liu, Jian; Zhang, Xiben; Ou, Maojun; Chen, Zelin; Li, Weibo; Zhao, Xingbo (Frontiers in Veterinary Science, 2021)
The domestication process exerts different phenotypic plasticity between slow- and fast-growing breeds of chicken. Feed restriction has a critical role in production performance, physiological plasticity, and stress response. Our study aimed to explore how feed restriction programed the organ index, dopamine, and hippocampal transcriptome profile between slow- and fast-growing chickens, which were fed either ad libitum (SA and FA), or feed restricted to 70% of ad libitum (SR and FR), for 30 days. Results showed that feed restriction influenced the brain organ index (P < 0.05), but not the organ index of the heart, liver, and spleen. The slow-growing breed tested had a higher brain organ index than the fast-growing breed (P < 0.05). Under feed restriction conditions, both the slow- and fast-growing breeds had significantly elevated dopamine concentrations (P < 0.05) compared to those fed ad libitum. In the GO term, upregulated genes in the FA group were enriched in the mitochondria, respiratory chain, and energy metabolism compared to the SA group (P < 0.05). Membranes and ribosomes were enriched in the cellular component between the SR and FR groups (P < 0.05). In the KEGG functional pathways, upregulated DEGs in the FR group were enriched in the cardiovascular disease category and neurodegenerative disease category compared to the FA group (P < 0.05). Downregulated DEGs in the FA group were enriched in the oxidative phosphorylation and neurodegenerative disease categories (Parkinson's disease and Huntington's disease) compared with the SA group (P < 0.05). Upregulated DEGs in the FR group were enriched in the cardiovascular disease category, neurodegenerative disease category, and energy metabolism than the SR group (P < 0.05). In conclusion, feed restriction had profound effects on the brain organ index and plasma dopamine in the slow- and fast-growing chickens. Feed restriction may result in issues relating to cardiovascular and neurodegenerative diseases in the fast-growing breed tested, but not in the slow-growing breed.